2014
DOI: 10.1002/asi.23187
|View full text |Cite
|
Sign up to set email alerts
|

Eye‐tracking analysis of user behavior and performance in web search on large and small screens

Abstract: In recent years, searching the web on mobile devices has become enormously popular. Because mobile devices have relatively small screens and show fewer search results, search behavior with mobile devices may be different from that with desktops or laptops. Therefore, examining these differences may suggest better, more efficient designs for mobile search engines. In this experiment, we use eye tracking to explore user behavior and performance. We analyze web searches with 2 task types on 2 differently sized sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 34 publications
(76 reference statements)
2
55
0
Order By: Relevance
“…Examining behavioural e ects on mobile devices when interacting with SERPs has a racted much research as of late (e.g. [24][25][26]), and with each device capable of displaying a di erent number of results above-the-fold, recent research has shown that the RPP value can in uence the behaviour of searchers [17,25]. Understanding this behaviour can help guide and inform those charged with designing contemporary user interfaces.…”
Section: Results Per Pagementioning
confidence: 99%
See 1 more Smart Citation
“…Examining behavioural e ects on mobile devices when interacting with SERPs has a racted much research as of late (e.g. [24][25][26]), and with each device capable of displaying a di erent number of results above-the-fold, recent research has shown that the RPP value can in uence the behaviour of searchers [17,25]. Understanding this behaviour can help guide and inform those charged with designing contemporary user interfaces.…”
Section: Results Per Pagementioning
confidence: 99%
“…Furthermore, we only considered how behaviours changed on the desktop, rather than on other devices where users are more likely to be sensitive to such changes (e.g. [25,27]). For example, during casual leisure search, multiple relevant documents on tablet devices are o en found, and so it would be interesting to perform a follow up study in this area.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…On small screens, we can discriminate search behaviour [59] and mobile learning preferences [60]. For eLearning in general, we can discover how the mode of presentation of the texts read affects learning outcomes [61].…”
Section: Reading and Elearningmentioning
confidence: 99%
“…With the rapid increase in the popularity of smart phones, mobile Internet usage has soared by 67% from Sept., 2013 to Aug., 2014, and the use of hand‐held devices (i.e., mobile phones and tablets) has grown rapidly from 21.9% to 35.3% worldwide, while accessing the web by using desktops remains at 64.6% (Statcounter Global Stats, ). From previous studies that compared user behavior and search performance on a desktop monitor versus a mobile device screen (Jones, Buchanan, & Thimbleby, ; Kim, Thomas, Sankaranarayana, Gedeon, & Yoon, ), it is believed that the interface design for web searches on mobile devices needs to be different from that on a desktop monitor. Therefore, there have been efforts to improve design by understanding user interaction with small devices (Guo, Jin, Lagun, Yuan, & Agichtein, ; Lagun, Hsieh, Webster, & Navalpakkam, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this article, we explore user web‐search performance and behavior on three different sizes of screens (3.6, 4.7, and 5.5 inches for earlier smart phones, recent smart phones, and phablets, respectively, as shown in Figure ) using eye‐tracking technology. We adopt search speed, search accuracy, and user satisfaction as the user performance metrics, similarly to previous studies (Kim et al., ; Lagun et al., ) and employ implicit data such as fixation and scanning patterns on SERPs to understand user behavior.…”
Section: Introductionmentioning
confidence: 99%